Recombination is required for efficient HIV-1 replication and the maintenance of viral genome integrity - Rawson, Jonathan M O (Nucleic Acids Res, 2018)
Retroviruses package two complete RNA genomes into a viral particle but generate only one provirus after each infection. This pseudodiploid replication strategy facilitates frequent recombination, which occurs during DNA synthesis when reverse transcriptase switches templates between two copackaged RNA genomes, generating chimeric DNA. Recombination has played an important role in shaping the current HIV-1 pandemic; however, whether recombination is required for HIV-1 replication is currently unknown. In this report, we examined viral replication when recombination was blocked in defined regions of the HIV-1 genome. We found that blocking recombination reduced viral titers. Furthermore, a significant proportion of the resulting proviruses contained large deletions. Analyses of the deletion junctions indicated that these deletions were the direct consequence of blocking recombination. Thus, our findings illustrate that recombination is a major mechanism to maintain HIV-1 genome integrity. Our study also shows that both obligatory and nonobligatory crossovers occur during reverse transcription, thereby supporting both the forced and dynamic copy-choice models of retroviral recombination. Taken together, our results demonstrate that, in most viruses, both packaged RNA genomes contribute to the genetic information in the DNA form. Furthermore, recombination allows generation of the intact HIV-1 DNA genome and is required for efficient viral replication.